THE ONLINE LEARNING MODEL OF EDUCATION AS A COVID-19 IMPACT FOR PAUD STUDENTS: HOW TO MEASURE ITS SUCCESS? - Irmawati, Noer Doddy (International Journal of Research -GRANTHAALAYAH, 2020)
The title mentioned above is discussed to overcome the difficulties of learning when facing Covid-19 for PAUD (Early Childhood Education Students) in Indonesia because they are the basic and the main level for success in Education. In fact, with the change from studying at school to learning at home, many parents face problems and difficulties, not just the teacher as a delivery of material to students and as teachers. The changes that occur are very sudden without proper preparation, because the arrival of the covid-19 pandemic is also very sudden. However, teachers and parents are required to be able to overcome the problem of learning and education for students as the successor to the nation in order to be able to successfully achieve future achievements for their future. The learning model is created immediately and by adjusting the situation, reality and situation. The model used is the Online and Environmental models. Over time learning in the face of a covid-19 pandemic, is faced with a focus that needs to be overcome and must be completed simultaneously. How learning can take place well, success according to objectives, and measuring learning success are also special things that need attention. How to measure the success of online learning at home is needed, because by measuring what has been done so far through direct teacher observation it is not possible to do, because students learn at home, so the role of parents is crucial. Therefore, in this paper, it is necessary to find out how to measure the success of PAUD students in their studies at home under the supervision of parents and deal directly with the main school with the teacher.